Fundamentals and challenges of optical multiple-input multiple-output multimode fiber links. - Tarighat, Alireza (IEEE Communications magazine)
In this article we discuss the application of MIMO processing to multimode fiber links. MIMO processing is shown to increase the information capacity of communication links linearly as the minimum number of transmitters/receivers increases. The fundamentals of optical MIMO fiber links are presented, and the promises and challenges of such systems are elaborated.